Surgical Management of Post-Intubation Tracheal Injuries: A Single-Center Experience from Nepal - Sapkota, Ranjan; Shrestha, Bibhush; Sharma, Aakriti (Journal of Institute of Medicine Nepal, 2022)
Introduction Despite various improvements in technology and patient care, tracheal intubation and tracheostomy still result in significant tracheal injuries like stenosis and airway fistula. Pressure necrosis by the inflated balloon is the commonest culprit. Post-intubation tracheal stenosis is a major indication for tracheal resection and anastomosis. This study was done to find out the indications and results of surgery for post-intubation tracheal lesions. Methods It was a descriptive observational study of patients with post-intubation tracheal lesions managed in Manmohan Cardiothoracic Vascular and Transplant Center over a period of 20 years (2001 to 2021). Results Twenty five patients were treated for post-intubation tracheal lesions. Four had isolated tracheo-esophageal fistula (TEF); eighteen had an isolated tracheal stenosis and three had both. Most had a tracheal resection and end-end anastomosis (REEA) via a cervical approach, resecting an average of 2.7 cm of tracheal length. The average size of stenotic lumen was 4.32 mm. There were no operative deaths. Two patients expired within a month of surgery: one due to fatal restenosis and the other due to sepsis. There were a few immediate and a few long-term complications. The average follow-up period was 5 years. Conclusion Among the various post-intubation lesions, tracheal stenosis is the commonest indications for surgery. The management is challenging but safe and feasible, with a multidisciplinary team approach.